PENGARUH KINERJA SOSIAL DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN - Ahmad Rosyid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
This study aimed to examine the effect of social andenvironmental performance’s disclosure on financial performance incompanies listed on the Stock Exchange under energy, mining and infrastructure industry sectors during 2010-2013.Using multiple regression method, the results show that environmental and social performance impact on the financial performance simultaneously while partially none of the independent variables affect the dependent variable. But the positive direction of their relationship is congruent with the theory. That is the better environmental and social performance then the better the financial performance.